(untitled) (The Review of Diabetic Studies, 2024)
Background: The globalization of healthcare and health data has intensified cross-border healthcare delivery, creating new opportunities for continuity of care while simultaneously exposing health systems to complex security threats. Nurses, as primary providers and custodians of patient data, occupy a pivotal role within this evolving landscape. However, the intersection between nursing practice and health security remains insufficiently explored in cross-border contexts. Aim: This paper aims to examine cross-border healthcare security challenges with a focused emphasis on nursing practice in the era of globalized health data, highlighting implications for patient safety, care quality, and global health system resilience. Methods: A narrative and conceptual analysis approach was employed, integrating literature from nursing science, health security, health informatics, and global health policy. The study synthesizes existing evidence to develop a nursing-centered framework for understanding and addressing cross-border health security risks. Results: The analysis identifies key health security challenges affecting nursing practice, including data privacy breaches, cybersecurity threats, regulatory fragmentation, ethical dilemmas in data sharing, and workforce mobility risks. These challenges directly impact patient safety through compromised confidentiality, data integrity failures, care disruptions, and erosion of trust. Nurses emerge as critical agents in mitigating these risks through ethical data stewardship, interprofessional collaboration, and frontline system engagement. Conclusion: Cross-border healthcare security is fundamentally dependent on nursing practice. Strengthening nursing-led health security through education, organizational leadership, and policy alignment is essential for safeguarding patient data, enhancing care quality, and sustaining trust in global healthcare systems. Integrating nursing perspectives into global health security frameworks is imperative for achieving resilient and equitable cross-border healthcare.